2014
DOI: 10.1371/journal.pone.0102542
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Iex-1 in the Pathogenesis of Venous Neointimal Hyperplasia Associated with Hemodialysis Arteriovenous Fistula

Abstract: Arteriovenous fistulas (AVFs) used for hemodialysis fail because of venous neointimal hyperplasia (VNH). There are 1,500,000 patients that have end stage renal disease worldwide and the majority requires hemodialysis. In the present study, the role of the intermediate early response gene X-1 (IEX-1), also known as IER-3 in the pathogenesis of VNH was evaluated. In human samples removed from failed AVF, there was a significant increase in IEX-1 expression localized to the adventitia. In Iex-1 −/− mice and wild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 47 publications
3
57
0
Order By: Relevance
“…Finally, a small pilot study using adventitial delivery of calcitriol, a 1,25-dihydroxyvitamin D3 and inhibitor of Iex-1, at the time of angioplasty showed reduction in venous stenosis formation (75). Similar results have been observed experimentally in Iex-1 knockout mice with AVF (76).…”
Section: Potential Future Molecular Targets That May Translate Into Tsupporting
confidence: 68%
“…Finally, a small pilot study using adventitial delivery of calcitriol, a 1,25-dihydroxyvitamin D3 and inhibitor of Iex-1, at the time of angioplasty showed reduction in venous stenosis formation (75). Similar results have been observed experimentally in Iex-1 knockout mice with AVF (76).…”
Section: Potential Future Molecular Targets That May Translate Into Tsupporting
confidence: 68%
“…30 With a similar jugular-to-carotid AVF model in mice with chronic renal failure, Misra reported lex-1 regulates MCP-1, with lex-1 KO mice having reduced MCP-1 and neointimal hyperplasia. 31 Our data shows no increase in MCP-1 RNA and protein expression, as well as fewer MCP-1-positive cells, in the AVF of CD44 KO mice (Figure 3), suggesting that one function of CD44 is to promote macrophage accumulation in the maturing AVF limb. However, it is also noteworthy that the increase in macrophages at day 21 is preceded by increased MCP-1 expression at day 7 (Figure 3).…”
Section: Discussionmentioning
confidence: 58%
“…Recently, elastin deposition within experimental fistulas has been described [19]. Local pharmaceutical delivery has been felt to be a potential strategy for treating access failure [9, 10, 20]. In fact, adventitial delivery of blood outgrowth endothelial progenitor cells has been shown to alleviate vascular injury associated with hemodialysis vascular access grafts [21].…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen days later, the same therapy was repeated using a separate surgical procedure [8]. Previously, experiments conducted using this technique have shown that venous stenosis forms in this model at the outflow vein [57, 911]. Seventy-nine male C57BL/6 mice weighing 25–30 grams underwent nephrectomy.…”
Section: Methodsmentioning
confidence: 99%